C'est quoi post-truth, new era or time-immemorial? Conceptual reflections for democracy, power and free speech. (March 2022) - Asardag, Dilara; Donders, Karen
As the hyped concept of post-truth began occupying various discourses of politicians, commentators and journalists in the recent years especially in the West, this article attempts to bring a critical reflection to the concept by carrying out an integrative literature review. Our aim is to critically examine and analyse the literature and main perspectives and relationships of the issue. Therefore, different perspectives of scholars and journalists who are well-versed in their domain/tradition are combined and integrated together. On the grounds that the emerging themes create a broader dichotomy and a field of tension between two broader views- post-truth as a new era and post-truth as time-immemorial or post-truth as unfolding through the years, the article will be divided into two main sections. This will be followed by further critical elaboration and discussion on the responses being taken regarding the "truth" of the "post-truth" phenomenon principally from the perspective of democracy, power and free speech.